Towards neglected tropical diseases elimination in Nigeria: addressing the stigma and mental health nexus - Precious Chidozie Azubuike; Uchenna Frank Imo; Chimankpam Kingsley Ogbonna; Temidayo Akinreni; Mark Daniel Udofia; Ogochukwu Jeremiah Odo; Miracle Nwadiche (Discover Social Science and Health)
Abstract Neglected Tropical Diseases (NTDs) are a public health challenge in Nigeria, especially within the marginalized populations; millions of people are affected. As much as biomedical interventions go a long way in the elimination of NTDs, stigma from these diseases forms a very strong barrier to care. It has profound mental health implications for affected individuals. Much of this stigma results from cultural myths and fear of contagion, leading to late health-seeking behavior, social isolation, and discrimination. These psychosocial factors, linked to an inadequate response from mental health services, seriously hinder effective treatment and control measures, increasing the burden of the disease. This paper discusses the relationship between stigma and mental health in NTDs and outlines gaps in the current health strategy while providing a comprehensive approach to deal with these pertinent issues. Combating NTDs and stigma requires a multifaceted approach, including training healthcare providers on the legal rights of those affected, community-level stigma reduction to improve health-seeking behaviors, and policy reforms. More importantly, by incorporating mental health services, reducing stigma, and improving health-seeking behavior, Nigeria will be advancing her efforts toward the goals of NTD elimination.